TATBIQ ṬARĪQAT AL-ʿĀB AL-LUGHAWIYYA AL-ʿARABIYYAH LI-TAḤSĪN MAHĀRAT AL-KALĀM WA-AL-KITĀBA LI-L-FAṢL AL-SĀBIʿ BI-MADRASAT AL-THANAWIYYA AL-MUʿALLIMĀT NAHḌAT AL-WAṬAN ANJĀNĪ LUMBUK AL-SHARQIYYA - Nailil Izzati Sa’adatul Asri; Abdul Aziz (Universitas Islam Negeri Mataram, 2023)
Language games consist of two words: